Influences of Organizational Goal Structures Upon Participant Evaluations - Tansik, David A. (Academy of Management Journal, 1973)
A field study tested the relationship between attributes of organizational goals and outputs and the nature of the criteria used in participant evaluations. The results of the study imply that similar types of tasks in different organizations may tend to be evaluated on the basis of different criteria depending upon the various organizations? goal structures.